Pulp Stem Cell-Mediated Functional Pulp Regeneration - Sui, B; Chen, C; Kou, X; Li, B; Xuan, K; Shi, S; Jin, Y (Journal of dental research, 2019)
The preservation of vital dental pulp with vasculature and nerve components remains one of the most significant challenges in modern dentistry. Due to the immense potential for neurovascularization, mesenchymal stem cell (MSC) transplantation has shown emerging promise in regenerative medicine and dental translational practice. Actually, pulp mesenchymal stem cells, including postnatal dental pulp stem cells (from permanent teeth) and stem cells from human exfoliated deciduous teeth, possess unique properties based on their origins from neural crest or glial cells. Furthermore, they reside in a neurovascular niche and have the potential for neurogenesis, angiogenesis, and neurovascular inductive activity. According to current pulp regeneration strategies, pulp stem cell-mediated approaches to regeneration have demonstrated convincing evidence that they can rebuild the complex histologic structure of native pulp in situ with highly organized physiologic patterns or even achieve de novo regeneration of complete dental pulp tissues. More importantly, recent clinical studies emphasized in situ neurovascularization outcomes in successful regeneration of vitalized pulp via pulp stem cell transplantation. In this review, we summarize recent breakthroughs in pulp stem cell-mediated pulp regeneration, emphasizing the crucial achievement of neurovascularization. This functional pulp regeneration represents an innovative and promising approach for future regenerative endodontics.